Pengaruh Substitusi Tepung Beras Ketan dengan Tepung Umbi Talas Bogor (Colocasia esculenta l schoott) terhadap Kualitas Dodol Susu Ditinjau dari Kualitas Fisik dan Kimia (Jurnal Ilmu dan Teknologi Hasil Ternak, 2016)
The purpose of this research was to determine the effect of substitution glutinous rice flour with Bogor tuber taroflour towards the best substitution improving the quality of end products which included physical quality (texture) and chemical qualities (fat, total sugar and reducing sugar) of milk sweetpastry. The materials used were fresh milk as the main ingredient, sugar, glutinous rice flour and Bogor tuber taroflour. The research method used was laboratory experiment with completely randomized design consisting of 5 treatments and 4 replications. Substitution treatment in the form of glutinous rice flour with Bogor tuber taroflour given on milk sweet pastry products covering P0 (100% glutinous rice flour and without Bogor tuber taroflour); P1 (75% glutinous rice flour and 25% Bogor tuber taro flour); P2 (50% glutinous rice flour and 50% Bogor tuber taro flour); P3 (25% glutinous rice flour and 75% Bogor taro tuber flour); P4 (without glutinous rice flour and 100% Bogor taro tuber flour). The results showed that there was highly significant difference effect (p<0.01) the substitution of glutinous rice flour with Bogor tuber taroflour to sugar reduction dodol taro milk with reduced sugar lows on P2 (16.66%), and significantly difference effect (p<0.05) dodol fat content milk with a fat content highs around 13.77% (P4), but did not significantly difference effect the total sugar and texture of milk sweet pastry. Substitution Bogor tuber taro flour 100% produced best quality of milk sweet pastry with texture value 10.12 N, fat content Â 3.44%, 44.71% total sugar and reducing sugar 5.64%.